Cultural and Institutional Determinants of Bilateral Trade Flows - Gert-Jan M. Linders; Arjen Slangen; Henri L.F. de Groot; Sjoerd Beugelsdijk (Tinbergen Institute, 2005)
This paper studies the intangible costs of international trade by extending the basic gravity equation with measures of cultural and institutional distance, and institutional quality. Analyzing a sample of bilateral trade flows between 92 countries in 1999, we find that institutional distance has a negative effect on bilateral trade, presumably because the transaction costs of trade between partners from dissimilar institutional settings are high. In contrast, we find that cultural distance has a positive effect on bilateral trade. A potential explanation for this finding is that firms prefer trade to host-country production in culturally distant countries. Finally, we find that the institutional quality of both the importer and exporter increases the amount of bilateral trade.
Keywords: F14; 330; trade; gravity model; cultural distance; institutions; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaft; Institutionelle Infrastruktur; Gravitationsmodell; Transaktionskosten